The potential in consortium of endophytic bacteria for controlling sheath blight by Rhizoctonia solani Kuhn in rice plants - Haliatur Rahma; Zurai Resti; Yusniwati Yusniwati; Fauzan Abid Hanif Nasution (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Rhizoctonia solani Kühn is a pathogenic fungus that causes sheath blight disease in rice. One effective strategy for managing this disease is the use of biological control, particularly through consortia of endophytic bacteria. This study aimed to identify the most effective endophytic bacterial consortium for suppressing sheath blight severity while also enhancing rice growth and yield. A Completely Randomized Design (CRD) was aemployed with six treatments, three replications, and three experimental units per treatment. The treatments included four bacterial consortia composed of combinations of Bacillus thuringiensis LmD13, Ochrobactrum intermedium LmB1, and Stenotrophomonas maltophilia LmB35, along with positive and negative controls. The experiment involved treating rice seeds and soaking seedling roots with the bacterial consortia before transplanting. R. solani was inoculated onto the rice leaf sheaths 40 days after planting. The effectiveness of each consortium as a biocontrol agent was evaluated based on incubation period, disease incidence, disease severity, and the area under the disease progress curve (AUDPC). Their biostimulant potential was assessed through parameters related to seedling growth, plant development, and yield. Results indicated that the endophytic bacterial consortia effectively suppressed sheath blight and significantly improved rice growth and production. Notably, the consortium of B. thuringiensis LmD13, O. intermedium LmB1, and S. maltophilia LmB35 extended the incubation period to 35 days post-inoculation and reduced disease incidence, severity, and AUDPC to 22.22%, 0.29%, and 1.01, respectively. This consortium also enhanced rice yield, with fresh and dry grain weights reaching 72.78 g and 63.02 g, respectively, compared to the positive control. These findings suggest that this bacterial consortium holds strong potential as a biocontrol agent and yield enhancer in rice cultivation.